2021
DOI: 10.1093/nar/gkab415
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modification of RNA m6A demethylase ALKBH5 regulates ROS-induced DNA damage response

Abstract: Faithful genome integrity maintenance plays an essential role in cell survival. Here, we identify the RNA demethylase ALKBH5 as a key regulator that protects cells from DNA damage and apoptosis during reactive oxygen species (ROS)-induced stress. We find that ROS significantly induces global mRNA N6-methyladenosine (m6A) levels by modulating ALKBH5 post-translational modifications (PTMs), leading to the rapid and efficient induction of thousands of genes involved in a variety of biological processes including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 80 publications
3
126
1
Order By: Relevance
“…Interestingly, our study indicated that m6A demethylase ALKBH5 overexpression could curb cell proliferation by decreasing the protein expression of CyclinD1. However, ALKBH5 overexpression had no effect on cell apoptosis, which was inconsistent with a recent study [ 46 ]. We considered that this inconsistency was caused by the environment and cell lines.…”
Section: Discussioncontrasting
confidence: 98%
“…Interestingly, our study indicated that m6A demethylase ALKBH5 overexpression could curb cell proliferation by decreasing the protein expression of CyclinD1. However, ALKBH5 overexpression had no effect on cell apoptosis, which was inconsistent with a recent study [ 46 ]. We considered that this inconsistency was caused by the environment and cell lines.…”
Section: Discussioncontrasting
confidence: 98%
“…Furthermore, phosphorylated ALKBH5 further promotes the interaction between ALKBH5 and small ubiquitin-related modifier (SUMO)ylated E2 UBC9. At the same time, the ERK/JNK/ALKBH5 PTM/m6A axis was activated in hematopoietic stem/progenitor cells (HSPCs), which also contributed to maintaining stable genomic integrity and thereby participated in the DNA damage response ( Yu et al, 2021 ). In addition, in other studies, ALKBH5 is closely associated with sentrin/SUMO-specific proteases 1 and 3 (SENP1 and SENP3) under oxidative stress ( Xu et al, 2008 ; Huang et al, 2009 ; Wang et al, 2012 ).…”
Section: Atherosclerosis and The M6a Ribonucleic Acid Modificationmentioning
confidence: 99%
“…It has been reported that m6A modification in RNA is an early step of the DNA damage response ( 40 , 41 , 42 , 43 ). For example, METTL3/14 and FTO transiently and dynamically regulate m6A modification at DNA damage sites and then recruit Pol κ to facilitate DNA repair following UV exposure ( 40 ).…”
Section: Discussionmentioning
confidence: 99%